The bohm-penrose-hameroff model for consciousness and free will theoretical foundations and empirical evidences - Bejar Gallego, Manuel (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
The Bohm-Penrose-Hameroff (BPH) model offers a heuristic explanation of consciousness from the complementary works of Bohm and Penrose-Hameroff. Physically, in the microscopic regime,the quantum neurology of Penrose and the quantum potential of Bohm play a unified role in the BPH model. Both, Bohm and Penrose look for an answer to the emergence of the classical regime from the quantum background of reality. In the biological level, Bohm’s macroneurons and Penrose’s microtubules work together as biophysical crucial elements to understand the consciousness phenomenon. The mindas an unconscious neural system to control the body in the environment, the arising of the conscious subject with self-perception in the whole reality, and the subjective sensation of free-will in the law-ruledworld, are some traditional philosophical problems that could be partially illuminated by the new biophysics of the BPH model.